Bimetallic platinum–bismuth nanoparticles prepared with silsesquioxane for enhanced electrooxidation of formic acid. (13th April 2015) - Chen, Tingting; Ge, Cunwang; Zhang, Yihong; Zhao, Qin; Hao, Furui; Bao, Ning
Abstract: Bimetallic platinum–bismuth nanoparticles (Pt-BiNPs) were prepared with octa-(3-amino-propyl) silsesquioxane (OA-POSS) for high-performance electrooxidation of formic acid. Characterization of nanoparticles revealed their homogeneous-phase with blackberry-like morphology when the fraction of Bi was no less than 60%. Their electrocatalytic activity was investigated with cyclic voltammetry and chronoamperograms. The prepared bimetallic Pt-BiNPs displayed larger electrochemical surface areas, better electrocatalytic activity and more favourable durability towards electrocatalytic oxidation of formic acid compared with commercial catalysts. The improvement might be ascribed to the role of OA-POSS as the control agent of morphology and the carrier of electrocatalyst with possible corrosive resistance. This study suggested that silsesquioxane might potentially facilitate preparation of homogeneous-phase nanoscaled catalysts for direct formic acid fuel cell in practical applications. Graphical abstract: Homogeneous-phase blackberry-like Pt–Bi nanoparticles were obtained using silsesquioxane as the control agent. The prepared nanoparticles displayed excellent performance, unique CO tolerance and long durability towards electro-oxidation of formic acid. Such Pt–Bi bimetallic nanoparticles might be a potential candidate applied in direct formic acid fuel cells. Highlights: Blackberry-like Pt–Bi nanoparticles were prepared with silsesquioxane. Silsesquioxane was used as morphology control agent with corrosive resistance. Homogeneous-phase Pt–Bi Nanoparticles shown high catalytic activity and stability. Bi could observably enhance CO tolerance of Pt–Bi nanoparticle for electrooxidation.